Sociolinguistics and language education - Hornberger, Nancy H (Multilingual Matters, 2010)
Includes bibliographical references and index.; This book provides an up-to-date overview of sociolinguistics, including topics of nationalism and popular culture, style and identity, creole languages, critical language awareness, multimodal literacies, classroom discourse, ideologies and power, across language education contexts ranging from the teaching of English as an international language to Indigenous language revitalization